2020
DOI: 10.1159/000511179
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Cerebrovascular Thromboembolic Complications in Three Young Patients

Abstract: Coronavirus disease 2019 (COVID-19) is a viral illness, caused by the novel severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). It is currently affecting millions of people worldwide and is associated with coagulopathy, both in the venous and arterial systems. The proposed mechanism being excessive inflammation, platelet activation, endothelial dysfunction, and stasis. As an ongoing pandemic declared by WHO in March 2020, health systems worldwide are experiencing significant challenges with COVID-19-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Overall, 57 CVT cases were collected from 28 reports (Table 1) [17–44]. Mean age was 53.5 years, with 11 cases presenting CVT at age <50 years and balanced gender distribution (50% female).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 57 CVT cases were collected from 28 reports (Table 1) [17–44]. Mean age was 53.5 years, with 11 cases presenting CVT at age <50 years and balanced gender distribution (50% female).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported CVT in patients asymptomatic for pulmonary or other systemic SARS‐CoV‐2 symptoms [36,40]. High‐resolution computerized tomography of the chest or chest x‐ray demonstrated abnormalities consistent with pulmonary COVID‐19 in 81% of cases (17/21), with only four patients reported to have normal findings (Table 1) [27,39,41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying mechanisms can be broadly categorized into diseases or procedures involving the thoracoabdominal aorta (aortic surgery, aortic dissection), Intrinsic arterial occlusion resulting from arteriosclerosis, vasculitis, infection, embolic occlusion, thrombosis, hypoperfusion and venous infarction. Our 1 st case had severe COVID-19 disease with likely underlying hypercoagulable state which trigged the thrombosis and acute brain and spinal cord infarctions [26] complicated by severe sepsis and hypoxemia. 2 nd case had neck message which triggered vertebral artery dissection leading to cervical cord infarction.…”
Section: Discussionmentioning
confidence: 81%